The Impact of Motivation Systems on Innovation and Investment Activity in Enterprises: Theoretical and Practical Assessment (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In the context of an increasingly competitive global economy, innovation and investment play a pivotal role in determining the sustainability and growth of enterprises. This paper explores the role of motivational systems in enhancing innovation and investment activities within organizations. Using a theoretical approach supported by international and local research findings, this study evaluates how motivation drives technological adoption, creative problem-solving, and employee engagement. The paper also examines Uzbekistan’s policy framework and legislative definitions of investment and motivation to highlight the importance of developing robust incentive mechanisms. The findings suggest that effective motivation systems significantly contribute to increased productivity, risk-taking, and innovation outcomes, ultimately leading to sustainable economic development.